Sprinting in road cycling - literature review - Merkes, P.; Mensapà, P.; Abbiss, C. (Journal of Science and Cycling, 2020)
A road cycling sprint can be described as the acceleration which occurs toward the end of competitions in order to reach the finish line in front of other competitors. The ability to sprint in road cycling is important since most races are decided in either a head-to-head, small group, or mass sprint finish. Cycling velocity during sprints is important. Factors influencing cycling velocity include the cyclist`s physiology, biomechanics and application of force, resistive forces caused by the environment, and the interaction between cyclists. To perform well in sprints, road cyclists are required to have a very well developed aerobic function but also extremely well established anaerobic capacity. Cyclists can produce higher power outputs while adopting a standing position when compared with a seated position, with professional male and female sprinters producing approximately 14.2 and 10.0 W/kg during road sprints which last 14 and 22 s, respectively. Additionally, lowering the torso and head during the standing sprint position results in an aerodynamicimprovement of around 25%. Before starting the sprint, road cycling sprinters can save energy by drafting behind other cyclists. However, being close to the front of the peloton during the last part of the race, together with several supporting teammates, is of high importance for cycling performance outcomes. Road cycling sprinting performance could be improved via increasing power output, reducing aerodynamic drag, and smart positioning in the peloton.